Structure of the 26S proteasome from Schizosaccharomyces pombe at subnanometer resolution - Bohn, Stefan (National Academy of Sciences, 2010)
The structure of the 26S proteasome from Schizosaccharomyces pombe has been determined to a resolution of 9.1 Å by cryoelectron microscopy and single particle analysis. In addition, chemical cross-linking in conjunction with mass spectrometry has been used to identify numerous residue pairs in close proximity to each other, providing an array of spatial restraints. Taken together these data clarify the topology of the AAA-ATPase module in the 19S regulatory particle and its spatial relationship to the α-ring of the 20S core particle. Image classification and variance analysis reveal a belt of high “activity” surrounding the AAA-ATPase module which is tentatively assigned to the reversible association of proteasome interacting proteins and the conformational heterogeneity among the particles. An integrated model is presented which sheds light on the early steps of protein degradation by the 26S complex.